Gamifikasi Dalam Kelas Bahasa Indonesia Bagi Penutur Asing (BIPA) Anak - Pratama, Fendy Yogha; Yuli Erviana, Vera; Iis Suwartini; Mixghan Norman Antono (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2025)
This case study aims to describe the implementation of gamification in an online BIPA (Bahasa Indonesia for Foreign Speakers) class and to analyze the ability of Danish learners to pronounce Indonesian vocabulary. The study was conducted with six learners aged 9–12 years in an online BIPA class organized by the Embassy of Indonesia in Denmark. Reflective notes and observation guidelines were used as instruments to collect data. Thematic data analysis revealed that gamification using Wordwall was implemented through five types of games: (1) Complete The Word, (2) The Hidden Words, (3) The Pacman Game, (4) Word Puzzles, and (5) Sentence Puzzles. Meanwhile, learners made four types of pronunciation errors: (1) sound addition, (2) sound omission, (3) sound alteration, and (4) code-switching. Based on these findings, further research is needed to determine whether these pronunciation errors also occur when learners write the vocabulary. Comprehensive knowledge of this issue will provide deeper insights into how such errors occur, enabling teachers to develop strategies to prevent recurring mistakes.